Análise de marcadores de hemólise em portadores de anemia falciforme - Mecabo, Grazielle [UNIFESP] (2015)
Hemolysis in Sickle Cell Anemia (SCA) is predominantly extravascular. The mechanism of removing abnormal or senescent erythrocytes, recently named eryptosis, depends on the exposure of classic erythrocyte phagocytosis signals (signals "eat me"), or signs that may inhibit their clearance by the reticuloendothelial system. Hemolysis also occurs by intravascular mechanismand is associated with the release of free Hemoglobin (Hb) in to the plasma. Haptoglobin and hemopexin proteins are needed to clear free Hb from the plasma. Hydroxyurea (HU), a drug that is used in the treatment of SCA, has among its effects ability to reduce hemolysis. However, little is known about how HU perform this important action. OBJECTIVES: To evaluate the importance of markers of hemolysis in patients with SCA in steady state, with or without the use of HU and those PATIENTS: 40 adult patients with SCA (36 diagnosed with SS and 4 S?0-thalassemia) who were being followed at the Hereditary Anemia Outpatient Clinic of EPM/UNIFESP were evaluated. They were categorized into three groups: a) SS - patients without HU in steady state (N = 20); b) SS-HU -who were using maximum tolerated dose of HU (N = 20). In addition, the control group (CG, N = 22) consisted of apparently healthy hemoglobin AA individuals. The study was approved by the Institution Research Ethics Committee and all patients gave written informed consent. Pregnant women and those on chronic transfusion were excluded from the study. METHODS: Laboratory evaluation: performed included complete blood count, reticulocyte count (Ret), estimation of fetal hemoglobin, indirect serum bilirubin, lactate dehydrogenase (LDH) isoforms and free plasma Hb (free-Hb), haptoglobin (Hp). Expression of band-3, phosphatidylserine, CD47, microvesicles, CD59, were evaluated by flow cytometry (FACSCalibur®, CellQuest Software, Becton Dickinson Biosciences®). Statistical analysis: It was performed by Kruskal-Wallis test and Spearman correlation, with a significance level of 5%. RESULTS/DISCUSSION: As expected, patients groups (SS and SS-HU) had markers of hemolysis significantly different from the control group. LDH showed strong negative correlation with Hp positive and free-Hb, confirming its role as a marker of intravascular hemolysis. The LDH-1, -2 and -3 isoforms showed strong positive correlation with free-Hb, suggesting that LDH-3, though still poorly understood, may also be a useful marker of hemolysis. The expression of band-3 was significantly increased in SS-HU when compared to the other groups analyzed. CD59 expression on RBCs was different among the groups studied, SS-HU showed the highest value and CG the lowest one.